Analysis of attacking corner kick strategies in the FA women`s super league 2017/2018 - Beare, H.; Stone, J. A. (International Journal of Performance Analysis in Sport, 2019)
This study describes how corner kicks were taken across the 2017/2018 FA Women`s Super League season and assesses the effectiveness of these attacking corner kick strategies. A total of 824 corner kicks were analysed examining delivery type, delivery area and attack organisation on corner kick outcomes. A total of 38 goals were scored (4.6% of corners taken resulted in a goal) from the corner kicks, accounting for 13.5% of the total 282 goals scored during the 2017/2018 season. Corner delivery type did not affect the outcome of the corner (p > 0.05). However, delivery zone effected both the likelihood of an attempt on target (p = 0.018) and goal being scored (p < 0.001). Attempts on target were increased when the ball was delivered into the central area of the 18-yard box (zone CA2) with 14.7% of corners delivered to CA2 resulting in an attempt on target. Goals were most likely to be scored when the ball was delivered into the central zone but closer to the goal line (zone GA2) with 13.0% of corner kicks delivered to this zone resulting in a goal. These results can aid coaches to enhance the attacking effectiveness of corner kicks within Women`s soccer.